KONDISI RUANGAN KERJA PADA TIGA PABRIK KAYU LAPIS DI SUMATRA SELATAN - Maman Mansyur Idris; Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
An investigation on working conditions of three plywood factories in South Sumatra was conducted in 1987; The objective is to find out the workers judgement about their working conditions in terms of conveniences.The total of 265 respondents from plywood factories employed in the processing steps of wood preparation, peeling, reeling, unreeling, veneer drying, veneer preparation, gluing, pressing, finishing, quality control, packaging, workshops and laboratories were interviewed.The results showed that in each processing step, more than 60% respondents felt their working space conditions were far from being convenient due to inappropriate air circulation, dust, bad smell noise, and vibration.